CARCASS CHARACTERISTICS, QUALITY OF MEAT AND CHEMICAL COMPOSITION OF MEAT LLAMA: A REVIEW - Mamani-Linares, Lindon W. (2014)
Llama meat has a high protein level and low cholesterol and lipid levels. The aminoacids profile is similar to other ruminants. The fatty acid profile is characterized by moderatelevels of saturated fatty acids and high levels of monounsaturated fatty acids and lowlevels of polyunsaturated fatty acids. The carcass of animals from 36 to 44 months of age is the most suitable for commercial cuts, while meat from older animals, based on theirtechnological characteristics, is more suitable for the manufacture of meat products.Carcasses of young llamas are characterized by low weight, poor conformation and littlefat cover. Feed supplementation in young animals helps improve carcass quality andperformance of commercial cuts, as well as meat quality.